Toxicological interactions between spinosad and essential oils in the Mediterranean fruit fly, Ceratitis capitata - Cortez-Vega, Ana (2023)
In recent decades, the use of biopesticides for pest management has increased, espe cially in modern and organic agriculture. Spinosad is a biopesticide approved in many countries for its use against Ceratitis capitata. However, an increasing amount of pest resistance against spinosad had been found in different pest species. In the present study, we propose the use of a combination between essential oils (EOs) and spinosad as a way to contribute to the development of sustainable alternatives, integrating natural substances with anti-insect properties and reducing the amount of commer cial active ingredients by synergistic effects. Our primary objective was to investigate the synergistic potential of EOs and spinosad in order to enhance the insecticidal ef ficacy against C. capitata adults. We evaluate the toxic effect of the EOs of Baccharis spartioides (Hook), Eucalyptus cinerea (F. Muell. ex Benth) and Schinus areira (Linneo), the bioinsecticide spinosad and their combinations. We evaluated the combined tox icities of EOs from B. spartioides, E. cinerea and S. areira with spinosad and character ized the LD50 of each mixture and each substance administered topically alone on male and female individuals of C. capitata. A synergistic effect was observed for the B. spartioides–spinosad mixture in females and the S. areira–spinosad mixture in both sexes, and an antagonistic effect was found for the B. spartioides–spinosad mixture and the E. cinerea–spinosad mixture in males. Considering these results, we suggest the use of the EO from S. areira combined with spinosad as an alternative way of con trolling C. capitata.